2014
DOI: 10.1007/s10103-014-1608-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of melasma with mixed parameters of 1,064-nm Q-switched Nd:YAG laser toning and an enhanced effect of ultrasonic application of vitamin C: a split-face study

Abstract: Melasma is an acquired pigment disorder showing symmetrical hyperpigmentation of the face characterized by light to dark brown patches with indistinct borders on both cheeks. Melasma is prevalent in middle-aged women with harmless hormone imbalances. It is also known as the mask of pregnancy and is prevalent in most child-bearing women. It fluctuates month by month, and yet, there is no promising treatment. The Q-switched neodymium-doped yttrium aluminum garnet (QS-Nd:YAG) laser (1,064-nm wavelength) was intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 15 publications
0
52
0
Order By: Relevance
“…Since 2007, 1064‐nm Q‐switched neodymium‐doped yttrium aluminium garnet (QS‐Nd:YAG) laser toning has been commonly prescribed for the treatment of melasma . However, in Asians, this treatment typically only produces temporary improvements along with certain side‐effects such as recurrence, hypopigmentation and rebound hyperpigmentation .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, 1064‐nm Q‐switched neodymium‐doped yttrium aluminium garnet (QS‐Nd:YAG) laser toning has been commonly prescribed for the treatment of melasma . However, in Asians, this treatment typically only produces temporary improvements along with certain side‐effects such as recurrence, hypopigmentation and rebound hyperpigmentation .…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [5] tried to combine both 1,064 nm Q-switched Nd-YAG laser and ultrasonic application (1 MHz, 0.5 W/cm 2 ) of topical vitamin C (5 ml of 20% L-ascorbic acid gel) for patients with melasma. They used 1,064 nm Q-switched Nd-YAG laser with the 8 mm spot size, 2.0 J/cm 2 for one pass then shifted to 6-mm spot size, 3.5 J/cm 2 for a second pass, and ended with 4 mm spot size, 3.2 J/cm 2 scanning mode for the final pass for full face and multiple additional passes for deep pigmented area till the endpoint of mild erythema and swelling.…”
Section: Melasmamentioning
confidence: 99%
“…Most commonly used whitening agents include azelaic acid and the triple combination (TC) cream containing 4% hydroquinone, 0.05% tretinoin, and 0.01% fluocinolone acetonide. 18,19 Combining laser toning with vitamin C iontophoresis 20 or peeling agents 16,21 has also been reported to bring favorable synergistic effects.…”
Section: Combination Therapy With Laser Toning (Excepting Other Lasermentioning
confidence: 99%
“…Among clinicians, the synergistic effect of combining vitamin C iontophoresis and laser toning has been recognized for a long time. Lee et al 20 found that the thermal effect of laser increased blood circulation of the skin and improved penetration of topical vitamin C.…”
Section: Combination Therapy With Laser Toning (Excepting Other Lasermentioning
confidence: 99%